Audio Visual Media to Improve Learning Achievement of Natural Science Subject in Earth Rotation Topic - Aan Rahmadhani (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Learning activites is a sending process of information from teacher to students. In order to create a meaningful learning proces, the information can be sent by using a learning media. It must be able to convey from an abstract theory that can received by sense onto a concrete one that can give a new learning experience for the students. A lesson about rotation of the earth, apart of natural science subject, is an abstract one that have to serve in the concrete point by the teacher in a classroom. Aims of study are describe concept of audio visual learning media,natural science subject such as rotation of the earth, and learning achievement of students about studying rotation of the earth in order using audio visual learning media. The results of this study is learning achievement of the students can be increased by using audio visual media in the learning process of studying natural science subject in topic about rotation of the earth.